Tres mujeres para una O.R.G.I.A artistica : nuevos lenguajes didácticos para una educación en valores basados en el arte feminista y queer - Palazón Cascales, Bartolomé (2019)
O.R.G.I.A. is an artistic group formed by Beatriz Higón, Carmen Muriana and Tatiana Sentamans. They first started in 2001. Both its artistic creation and research focus on genre, sex and sexuality matters, defining themselves as feminists and queers. It is a multidisciplinary team that has used performance, video, sculpture, drawing and illustration to develop its artistic production. This artistic production has a marked political nature and a clear activist objective, as well as a strong fighting spirit and criticism. It pursues the dissolution of the normative concepts in terms of gender, sexuality and sex, seeking hybridization and inclusion to avoid labels and sealed categories